The Ecology of the "Terroir": What Can an Old French Concept Bring to Modern Relationships to the Land? - Ducarme, Frédéric (Environmental ethics, 2025)
Industrial agriculture led to a worldwide homogenization of crops and modes of cultures, but also of landscapes and relationships to the land, threatening at the same time biodiversity and cultural diversity. Developing alternatives to the agro-industrial system inherited from the twentieth century is therefore one of the greatest challenges facing humankind today. This article advocates for the promotion of the French concept of "terroir" as a foundational framework for preserving biocultural diversity, illustrating an ethical way of relating to the land. Already enshrined in European law for three decades and under study at the UNESCO and the FAO, it encourages farmers to adopt ecologically virtuous practices, while ensuring greater economic incomes. Moreover, it enhances the value of their work and their specific relationship with their environment in the long run. It also epitomizes broader worldwide initiatives, which propose basing agriculture not against the environment (both human and natural) but in symbiosis with it.